Cloning and identification of human colipase-like 3 and its homologous cDNAs - LU Yan; XUE Yong-chang; YU Peng; WANG Ping-zhang (浙江大学学报. 农业与生命科学版)
Although ten years have passed since the draft sequence of the human genome was reported in 2001, the accurate number of human protein-encoding genes is still uncertain. According to the latest release of H-InvDB (release 6.2), 34511 protein-encoding genes were annotated and most of them were function-unknown. There is still a long road ahead to identify the whole human genes and their functions. During our previous genome-wide analysis of single-block EST sequences with polyadenylation sites, we found a lot of ESTs that represented potentially novel un-identified genes or splice variants. In the present study, we focused on the cloning and identification of a novel cDNA sequence represented by the EST AV 653338 with the encoding product containing two incomplete colipase-like domains, when the electronic prolongation by EST contig was performed.By using mixed cDNAs from human cell lines as templates, we successfully cloned the novel encoding gene sequence, and revealed a novel human colipase-like protein-encoding gene named hCLPSL3 (human colipase-like 3) for there have been two other genes with protein products also containing colipase-like domains registered in the international nucleotide databases, C6ORF126 (namely CLPSL1 here) and C6ORF127 (namely CLPSL2 here). Totally, two transcript variants were obtained, i.e. hCLPSL3-v1 and -v2. Only hCLPSL3-v1 contained a complete open reading frame (ORF), encoding 159 amino acids, whereas the ORF of hCLPSL3-v2 was interrupted by PTC (premature stop codon) and it possibly was a substrate of nonsense-mediated mRNA decay. Human CLPSL3-v1 contained a typical signal peptide (aa. 1-22) predicted by SignalP 4.0 Server, two internal sequence repeat regions (aa. 46-84 and aa.88-125) with high homology, and two incomplete colipase-like domains (aa. 25-68 and aa. 113-159) predicted by InterProScan and Motif Scan program, respectively. Using nested RT-PCR method for expression analysis in several cell lines (293T, HeLa, U2OS, HepG2, HCT116, A549, H1299, Jurkat, H520 and THP-1), we found that hCLPSL3 was mainly expressed in 293T, U2OS, HCT116 and THP-1 cells. For lack of cDNAs, we did not perform the detection in human tissues. The typical signal peptide in CLPSL3 suggests that it probably is a secreted protein. Therefore, the recombinant eukaryotic expression vector of hCLPSL3-v1 was constructed, and over-expressed in human 293T cells. As expected, human CLPSL3 was verified to be secreted when the supernatant was used for Western blot assay. By homology analysis, mouse and rat CLPSL3 homologous cDNAs were also predicted. Using RT-PCR method, three mouse CLPSL3 transcript variants (mCLPSL-v1, -v2 and -v3) were successfully cloned in the kidney (-v1), colon (-v2) and spleen (-v3) tissues, respectively. Only mCLPSL-v1 contained a complete ORF encoding 161 amino acids, whereas the ORFs of both mCLPSL-v2 and -v3 were interrupted by PTCs. Rat CLPSL3 (rCLPSL3) cDNAs, encoding a product of 162 amino acids, were successfully cloned in both colon and small intestine tissues. However, rCLPSL 3 was undetectable in rat pancreas. CL PSL3 was widely expressed and highly conserved in mammalian animals, such as Pan troglodytes, Equus caballus, Cavia porcellus, Loxodonta africana, Mus musculus and Rattus norvegicus, and showed very similar gene structures. Moreover, the CLPSL3 contained 18 highly conserved cysteines in all species, suggesting that it might relate to the disulfide bond formation.Colipase is a co-factor needed by pancreatic lipase for efficient dietary lipid hydrolysis. Because both mCLPSL and rCLPSL3 were detectable for expression in digestive tract, whether they play important roles in dietary lipid hydrolysis still needs further investigation. Our studies lay a foundation for future functional study of CLPSL3. In addition, all of the novel nucleotide sequences have been submitted to GenBank database with the accession numbers: JQ012741 (hCLPSL3-v1), JQ012742 (hCLPSL3-v2), JQ258939 (mCLPSL-v1), JQ258940 (mCLPSL-v2), JQ258941 (mCLPSL-v3) and JQ258942 (rCLPSL3).